Communicative barriers and resources in nursing homes from the enrolled nurses' perspective: A qualitative interview study. (February 2016) - Forsgren, Emma; Skott, Carola; Hartelius, Lena; Saldert, Charlotta
Abstract: Background and objectives: Managing communicative disability is a pervasive issue in long-term care facilities. The aim of this study was to explore how enrolled nurses experience their everyday interactions with residents in nursing homes, particularly focusing on interactions with residents with communicative disability. Design: A qualitative exploratory design including content analysis was used. Participants and setting: Eight individuals working at six nursing homes in western Sweden were interviewed. Method: The interviews were semi-structured with questions about the participants' experiences in communicating with residents, feelings associated with interactions involving residents with communicative disability, meaning ascribed to interactions, and factors influencing interactions. The interviews were analysed using content analysis. Results: A dynamic interplay between interpersonal relations, daily interactions and the managing of communicative disability was revealed. The enrolled nurses had good knowledge of supportive strategies and an awareness of the importance of the development of personal relationships with residents in order to facilitate interaction. However, factors in the environment presented barriers to communication. Conclusions/implications: The organisation and physical environment of nursing homes prevent the enrolled nurses from taking full advantage of the communicative resources they have in interaction with residents with communicative disability, hence affecting staff–resident relationships and the delivery of person-centred care.